Clinical Validation of a Novel High-Sensitivity Cardiac Troponin I Assay for Early Diagnosis of Acute Myocardial Infarction. (1st September 2018) - Boeddinghaus, Jasper; Twerenbold, Raphael; Nestelberger, Thomas; Badertscher, Patrick; Wildi, Karin; Puelacher, Christian; du Fay de Lavallaz, Jeanne; Keser, Elif; Rubini Giménez, Maria; Wussler, Desiree; Kozhuharov, Nikola; Rentsch, Katharina; et al.
Abstract: BACKGROUND: Clinical performance of the novel high-sensitivity cardiac troponin I (Siemens-hs-cTnI-Centaur) assay is unknown. We aimed to clinically validate the Siemens-hs-cTnI-Centaur assay and develop 0/1-h and 0/2-h algorithms. METHODS: We enrolled patients presenting to the emergency department with symptoms suggestive of acute myocardial infarction (AMI). Final diagnoses were centrally adjudicated by 2 independent cardiologists including all clinical information twice: first, using serial hs-cTnT (Roche-Elecsys, primary analysis); second, using hs-cTnI (Abbott-Architect, secondary analysis) measurements in addition to the clinically applied (hs)-cTn. Siemens-hs-cTnI-Centaur was measured at presentation, 1 h, and 2 h. The primary objective was a direct comparison of diagnostic accuracy, quantified by the area under the ROC curve (AUC), of Siemens-hs-cTnI-Centaur vs the 2 established hs-cTn assays (Roche-hs-cTnT-Elecsys, Abbott-hs-cTnI-Architect). Secondary objectives included the development of Siemens-hs-cTnI-Centaur-specific 0/1-h and 0/2-h algorithms. RESULTS: AMI was the final diagnosis in 318 of 1755 (18%) patients (using Roche-hs-cTnT-Elecsys for adjudication). The AUC at presentation for Siemens-hs-cTnI-Centaur was 0.94 (95% CI, 0.92–0.96) and comparable with 0.95 (95% CI, 0.93–0.97) for Roche-hs-cTnT-Elecsys and 0.93 (95% CI, 0.90–0.96) for Abbott-hs-cTnI-Architect. Applying the derived Siemens-hs-cTnI-Centaur 0/1-h algorithm to the validation cohort, 46% of patients were ruled out (sensitivity, 99.1%; 95% CI, 95.3–100), and 18% of patients were ruled in (specificity, 94.1%; 95% CI, 91.8–95.9). The Siemens-hs-cTnI-Centaur 0/2-h algorithm ruled out 55% of patients (sensitivity, 100%; 95% CI, 94.1–100), and ruled in 18% of patients (specificity, 96.0%; 95% CI, 93.1–97.9). Findings were confirmed in the secondary analyses using serial measurements of Abbott-hs-cTnI-Architect for adjudication. CONCLUSIONS: Diagnostic accuracy and clinical utility of the novel Siemens-hs-cTnI-Centaur assay are high and comparable with the established hs-cTn assays. ClinicalTrials.gov Identifier: NCT00470587